2021
DOI: 10.5829/ije.2021.34.04a.25
|View full text |Cite
|
Sign up to set email alerts
|

Experimental Study of Polyvinyl Alcohol Nanocomposite Film Reinforced by Cellulose Nanofibers from Agave Cantala

Abstract: This paper presents an experimental study of addition of cellulose nanofibers (CNF) extracted by the chemical-ultrasonication process from agave cantala leaf plants in the matrix of polyvinyl alcohol (PVA). Combining these materials produce the nanocomposite film with a thickness of 30 μm. The nanocomposite characteristic was investigated by the addition of CNF (0, 2, 5, 8, and 10 wt%) in PVA suspension (3 wt.%). PVA/CNF nanocomposite films were prepared by a casting solution method. The fibrillation of fibers… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(7 citation statements)
references
References 42 publications
(62 reference statements)
0
2
0
Order By: Relevance
“…Figure 8 shows that adding nanocellulose as a filler increased the elongation at the break of the PVA-chitosan films, which is similar to other report [79]. Hajii et al [11] found elongation at break pure PVA and chitosan are 38.4 and 454 %.…”
Section: Results Of Tensile Analysis Of Nanocomposite Filmsupporting
confidence: 85%
See 1 more Smart Citation
“…Figure 8 shows that adding nanocellulose as a filler increased the elongation at the break of the PVA-chitosan films, which is similar to other report [79]. Hajii et al [11] found elongation at break pure PVA and chitosan are 38.4 and 454 %.…”
Section: Results Of Tensile Analysis Of Nanocomposite Filmsupporting
confidence: 85%
“…Hydrogen bonds are formed in order to increase the strength of the polymer [78]. Yudhanto et al [79] has found that increasing nanocellulose composition from 2 to 5% lead to an increase in tensile strength. Moreover, Perumal et al [80] blended PVA-chitosan-nanocellulose and resulting tensile strength increase with an increase in nanocellulose composition (1, 3 and 5%).…”
Section: Results Of Tensile Analysis Of Nanocomposite Filmmentioning
confidence: 99%
“…Thus, the observation above shows that the input variables (T, ω, and S) will determine the distribution quality of clay particles on PA6/NBR blends. According to the XRD results, comparing X-ray diffraction patterns of the samples fabricated by FSP in this study and internal mixer [3,9] shows that the correct choice of friction stir process parameters can have a great effect on nanoparticle dispersion on the polymer matrix.…”
Section: Morphological Studies 2 1 Xrd Analysismentioning
confidence: 80%
“…Thermoplastic elastomers (TPEs) are defined as a collection of copolymers (such as plastic and rubber) that consist of materials with both elastic (related to rubber phase) and strength (related to plastic phase) properties [1,2]. They have a wide application in industry due to their ability to stretch, to moderate elongation and return to their near original shape, excellent thermal, mechanical, and chemical resistances [3,4]. In recent years, a lot of articles reported on mechanical properties and fracture mechanisms of TPE blends [5][6][7].…”
Section: Introductionmentioning
confidence: 99%
“…The highest intensity on the wave 3450 cm −1 shows the pure PVA film characteristic. The vibration band observed at 2928 cm -1 presence of intramolecular bond of C-H from the alkyl group [26][27][28]. Increasing the chitosan content in the PVA film reduces the intensity of the wave peaks.…”
Section: Ftir Analysismentioning
confidence: 98%